Pathogenicity and molecular characteristics of fowl adenovirus serotype 4 with moderate virulence in Guangxi Province, China - Wei, You; Xie, Zhixun; Fan, Qing; Xie, Zhiqin; Deng, Xianwen; Luo, Sisi; Li, Xiaofeng; Zhang, Yanfang; Zeng, Tingting; Huang, Jiaoling; Ruan, Zhihua; Wang, Sheng (Frontiers in Veterinary Science, 2023)
The GX2020-019 strain of fowl adenovirus serotype 4 (FAdV-4) was isolated from the liver of chickens with hydropericardium hepatitis syndrome in Guangxi Province, China, and was purified by plaque assay three times. Pathogenicity studies showed that GX2020-019 can cause typical FAdV-4 pathology, such as hydropericardium syndrome and liver yellowing and swelling. Four-week-old specific pathogen-free (SPF) chickens inoculated with the virus at doses of 103 median tissue culture infectious dose (TCID50), 104 TCID50, 105 TCID50, 106 TCID50, and 107 TCID50 had mortality rates of 0%, 20%, 60%, 100%, and 100%, respectively, which were lower than those of chickens inoculated with other highly pathogenic Chinese isolates, indicating that GX2020-019 is a moderately virulent strain. Persistent shedding occurred through the oral and cloacal routes for up to 35 days postinfection. The viral infection caused severe pathological damage to the liver, kidney, lung, bursa of Fabricius, thymus, and spleen. The damage to the liver and immune organs could not be fully restored 21 days after infection, which continued to affect the immune function of chickens. Whole genome analysis indicated that the strain belonged to the FAdV-C group, serotype 4, and had 99.7% to 100% homology with recent FAdV-4 strains isolated from China. However, the amino acid sequences encoded by ORF30 and ORF49 are identical to the sequences found in nonpathogenic strains, and none of the 32 amino acid mutation sites that appeared in other Chinese isolates were found. Our research expands understanding of the pathogenicity of FAdV-4 and provides a reference for further studies.